2010
DOI: 10.1002/lsm.20921
|View full text |Cite
|
Sign up to set email alerts
|

Effect of laser therapy on DNA damage

Abstract: This study shows a protective effect or DNA repair mechanism induction by pre-exposure to low intensity red laser on the lethal action of oxidant agents and, therefore, laser therapy protocol should consider fluencies, wavelength and tissue conditions before beginning treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
67
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 56 publications
(77 citation statements)
references
References 46 publications
10
67
0
Order By: Relevance
“…Laser exposure and zymosan-induced did cause neither DNA fragmentation nor cell death by caspase-6 pathway. Several studies have been reported controversial and possible adverse effects on cells and data about DNA damage after laser exposure in eukaryotic 42,43 and prokaryotic cells 32,[44][45] at different powers, wavelengths and fluences. In addition, as regard to DNA, a variety of studies have suggested that exposure to red and near infrared low-intensity lasers could induce adaptation or DNA damage at a sub-lethal level 32, 45 .…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Laser exposure and zymosan-induced did cause neither DNA fragmentation nor cell death by caspase-6 pathway. Several studies have been reported controversial and possible adverse effects on cells and data about DNA damage after laser exposure in eukaryotic 42,43 and prokaryotic cells 32,[44][45] at different powers, wavelengths and fluences. In addition, as regard to DNA, a variety of studies have suggested that exposure to red and near infrared low-intensity lasers could induce adaptation or DNA damage at a sub-lethal level 32, 45 .…”
Section: Discussionmentioning
confidence: 98%
“…On the other hand, low intensity lasers at therapeutic doses could induce free radicals generation 10 and sublethal DNA lesions 32 . Some studies have been reported the subcellular effects, such as phototherapy-induced apoptosis by mitochondrial pathway [33][34][35] .…”
Section: Discussionmentioning
confidence: 99%
“…Biological effects caused by free radicals from laser light are controversial and possible adverse effects on cells and data about DNA damage after laser exposure have been reported in eukaryotic [10][11][12][13][14] and prokaryotic cells [15][16][17][18][19][20][21][22][23] , at different powers, wavelengths and fluences. In addition, as regard to DNA, a variety of studies have suggested that exposure to red and near infrared low-intensity lasers could induce adaptation or DNA damage at a sub-lethal level.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, as regard to DNA, a variety of studies have suggested that exposure to red and near infrared low-intensity lasers could induce adaptation or DNA damage at a sub-lethal level. 16,18,[24][25][26][27] Chromatin organization changes, ploidy degrees and DNA fragmentation may be investigated by image analysis densitometry of Feulgen-stained nuclei, using geometric, densitometric and textural parameters. Feulgen reaction can be considered a sensitive method for the DNA evaluation in different cell types under various physiological and pathological conditions and it allows the reliable and rapid estimation of nuclear DNA contents.…”
Section: Introductionmentioning
confidence: 99%
“…The laser radiation energy is transformed in a primary photosignal and in sequence it is transduced and amplified into cells . It is thought that, in this transduction process, there is production of free radicals , and these reactive species could react with intracellular molecules, including DNA and membrane lipids .…”
Section: Introductionmentioning
confidence: 99%